Skate skiing stride energy efficiency: benefits of programmed dynamic electrical myostimulation - Rostovtsev, V. L.; Kryazhev, V. D. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to rate and analyze the skate skiing stride (quadriceps femoris push-off phase) energy efficiency with/ without programmed dynamic electrical myostimulation.